FRAMING THE LONG ARC: MODELING MEDIA INFLUENCE FROM CIVIL RIGHTS JOURNALISM TO DIGITAL ACTIVISM (Lex localis - Journal of Local Self-Government, 2025)
This article introduces the Media-Opinion Resonance Framework (MORF), a historically grounded model designed to assist journalism historians in analyzing the evolution of media influence over time. By drawing on case studies such as The Chicago Defender, Jet magazine’s coverage of the Emmett Till case, and archival reporting on the 1965 Selma campaign, MORF formalizes concepts of emotional framing, media trust, and message repetition into a structured analytical tool for examining shifts in public opinion.Rather than predicting behavior, MORF employs metaphorical simulations to illuminate how symbolic strategies have historically shaped emotional responses. It is complemented by a companion model, Media Influence and Public Response (MIPR), which incorporates patterns of consumer and civic engagement. Together, these models offer a reproducible method for exploring journalism’s enduring persuasive power.Rooted in archival research, MORF is historiographical in aim. It does not seek to replace traditional archival or narrative methodologies, but to enhance them by offering new interpretive clarity. By encouraging scholars to reassess landmark media events as dynamic influence systems—shaped by resonance, timing, and trust—MORF contributes to a deeper understanding of the interplay between media framing and public consciousness. This study adds to the discourse on American journalism by proposing a structured yet historically sensitive model for evaluating audience reception and press impact.